Analisis Fiqh Muamalah Terhadap Kemitraan Perajin Batik dan UMKM Di Kabupaten Bangkalan: Studi Kasus Perajin Batik Tulis Tanjung Bumi Kabupaten Bangkalan - Khoirun Nasik, Mahmudin, (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2021)
This study examines the partnership model and contract law applied by batik artisans and UMKM based on muamalah fiqh. The main problems in this study are: 1) How is the partnership practice of Batik craftsmen and UMKM in Tanjung Bumi District, Bangkalan Regency, 2) How is the fiqh muamalah analysis of Batik craftsmen and UMKM in Tanjung Bumi District, Bangkalan Regency. The research technique used in this research is qualitative with a critical paradigm approach, with primary data sources (research informants) and secondary (reference books). Collecting data through observation, interviews, and documentation. Informants in the study were sugarcane farmers and Takalar sugar mills. Interview data were analyzed using data analysis techniques carried out through data reduction, data presentation and then drawing conclusions. The results of the study can show that 1) The pattern of partnership or cooperation between batik craftsmen and UMKM is known as syirkah. Syirkah or Musyarakah is a cooperation agreement between two or more parties for a particular business in which each party contributes funds with an agreement that risks and profits will be borne according to a mutual agreement. 2) Fiqh muamalah as a result of managing human potential in achieving as many divine values ​​as possible, relating to the rules of human relations (makhluqat), which as a whole is a scientific discipline that is not easy to understand.